Polymeric ionic liquid promotes acidic electrocatalytic CO2 conversion to multicarbon products with ampere level current on Cu - Zhonghao Tan; Jianling Zhang; Yisen Yang; Jiajun Zhong; Yingzhe Zhao; Yunan Teng; Buxing Han; Zhongjun Chen (Nature Communications)
Abstract The acidic electroreduction of CO2 into multicarbon (C2+) products is much attractive for the improved carbon utilization than alkaline or neutral electroreduction. How to improve the efficiency of C2+ products generation by acidic electroreduction of CO2, is important, especially at high current density and in electrolyte with low K+ concentration. Herein, we propose a strategy of capping Cu surface with a polymeric ionic liquid (PIL) adlayer for boosting the acidic electrocatalytic CO2 conversion to C2+ products at high current densities (ampere-level) and low K+ concentration. In the electrolyte with a relatively low K+ concentration (1.0 M), the Faradaic efficiency (FE) for C2+ products reaches 82.2% under a current density 1.0 A·cm−2 in acidic environment (pH=1.8). Particularly, when the current density is as high as 1.5 A·cm−2, the C2+ FE still keeps 75.8%. Experimental and theoretical studies reveal that the presence of PIL adlayer on Cu catalyst can well inhibit H+ diffusion to catalyst surface, enrich more K+ and facilitate C-C coupling reaction.